On the Lathrobium fauna of China V. New species and additional records from Yunnan (Coleoptera: Staphylinidae: Paederinae). - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2013)
Material of the paederine genus Lathrobium Gravenhorst, 1802 from the Chinese province Yunnan is examined. Fifty-nine species are identified, nine of them described previously and fifty undescribed. Forty species are described and illustrated for the first time, all of them micropterous and locally endemic: Lathrobium abscisum sp. n. (Gaoligong Shan), L. acre sp. n. (Gaoligong Shan), L. acutapicale sp. n. (mountain range ESE Zhongdian), L. amputatum sp. n. (Gaoligong Shan), L. bidigitulatum sp. n. (Gaoligong Shan), L. bifasciatum sp. n. (mountain range SSE Zhongdian), L. bihamulatum sp. n. (Ertaipo Shan E Mangshi), L. biseriatum sp. n. (Xue Shan), L. breviseriatum sp. n. (mountain range E Weishan), L. curvatissimum sp. n. (Jizu Shan), L. desectum sp. n. (Gaoligong Shan), L. elevatum sp. n. (Ailao Shan), L. exspoliatum sp. n. (Xue Shan), L. fortehamatum sp. n. (Xue Shan), L. fortespinosum sp. n. (mountain range N Zhongdian), L. glandulosum sp. n. (Gaoligong Shan), L. grandispinosum sp. n. (Zhemo Shan), L. hirsutum sp. n. (Diancang Shan), L. iaculatum sp. n. (Gaoligong Shan), L. incurvatum sp. n. (mountain range SSE Zhongdian), L. magnispinosum sp. n. (Wuliang Shan), L. nuicum sp. n. (Nu Shan), L. puetzi sp. n. (Nu Shan), L. rastellatum sp. n. (Ailao Shan), L. rastratum sp. n. (Wuliang Shan), L. rectissimum sp. n. (Gaoligong Shan), L. resectum sp. n. (Gaoligong Shan), L. restinctum sp. n. (mountain range ESE Zhongdian), L. reticolle sp. n. (Haba Shan), L. schuelkei sp. n. (Laobie Shan), L. secans sp. n. (Gaoligong Shan), L. sectum sp. n. (Gaoligong Shan), L. seriespinosum sp. n. (Yulongxue Shan), L. sexspinosum sp. n. (Yulongxue Shan), L. squamosum sp. n. (Ertaipo Shan E Mangshi), L. stipiferum sp. n. (Haba Shan), L. tentaculatum sp. n. (Ailao Shan), L. tricuspidatum sp. n. (Haba Shan), L. triquetrum sp. n. (Bangma Shan), L. zhemoicum sp. n. (Zhemo Shan). Ten probably undescribed species remain unnamed, since only females have become available. Seven previously described species and the previously unknown female sexual characters of L. yulongense Peng & Li, 2012 are fully redescribed and illustrated. The Lathrobium fauna of Yunnan currently comprises fifty-eight described species and is thus far more diverse than those of other Chinese provinces. The total number of species recorded from mainland China now amounts to 156. All the Lathrobium records from Yunnan are from the west of the province, with the greatest diversity in the Gaoligong Shan (18 species). The known distribution of the genus in Yunnan and the individual distributions of 48 species are mapped. The examined material from Yunnan was collected primarily from leaf litter in various forest and shrub habitats at elevations between 2100 and 4100 m. The sex ratio of four species is strongly biased in favour of females, at least in one species apparently a result of different, sex-related life expectancies. Primarily based on their male and female sexual characters, the examined species are attributed to eight species groups, with one of them subdivided into eleven subgroups. Only three of these species groups also include species from other provinces (Sichuan, Chongqing); the distributions of the remainder are confined to Yunnan.KeywordsColeoptera, Staphylinidae, Paederinae, Lathrobiina, Lathrobium, Palaearctic region, China, Yunnan, taxonomy, new species, descriptions, redescriptions, species groups, endemism, glands, sex ratio, life history.Nomenclatural Actsabscisum Assing, 2013 (Lathrobium), spec. nov.acre Assing, 2013 (Lathrobium), spec. nov.acutapicale Assing, 2013 (Lathrobium), spec. nov.amputatum Assing, 2013 (Lathrobium), spec. nov.bidigitulatum Assing, 2013 (Lathrobium), spec. nov.bifasciatum Assing, 2013 (Lathrobium), spec. nov.bihamulatum Assing, 2013 (Lathrobium), spec. nov.biseriatum Assing, 2013 (Lathrobium), spec. nov.breviseriatum Assing, 2013 (Lathrobium), spec. nov.curvatissimum Assing, 2013 (Lathrobium), spec. nov.desectum Assing, 2013 (Lathrobium), spec. nov.elevatum Assing, 2013 (Lathrobium), spec. nov.exspoliatum Assing, 2013 (Lathrobium), spec. nov.fortehamatum Assing, 2013 (Lathrobium), spec. nov.fortespinatum Assing, 2013 (Lathrobium), spec. nov.glandulosum Assing, 2013 (Lathrobium), spec. nov.grandispinosum Assing, 2013 (Lathrobium), spec. nov.hirsutum Assing, 2013 (Lathrobium), spec. nov.iaculatum Assing, 2013 (Lathrobium), spec. nov.incurvatum Assing, 2013 (Lathrobium), spec. nov.magnispinosum Assing, 2013 (Lathrobium), spec. nov.nuicum Assing, 2013 (Lathrobium), spec. nov.puetzi Assing, 2013 (Lathrobium), spec. nov.rastellatum Assing, 2013 (Lathrobium), spec. nov.rastratum Assing, 2013 (Lathrobium), spec. nov.rectissimum Assing, 2013 (Lathrobium), spec. nov.resectum Assing, 2013 (Lathrobium), spec. nov.restinctum Assing, 2013 (Lathrobium), spec. nov.reticolle Assing, 2013 (Lathrobium), spec. nov.schuelkei Assing, 2013 (Lathrobium), spec. nov.secans Assing, 2013 (Lathrobium), spec. nov.sectum Assing, 2013 (Lathrobium), spec. nov.seriespinosum Assing, 2013 (Lathrobium), spec. nov.sexspinosum Assing, 2013 (Lathrobium), spec. nov.squamosum Assing, 2013 (Lathrobium), spec. nov.stipiferum Assing, 2013 (Lathrobium), spec. nov.tentaculatum Assing, 2013 (Lathrobium), spec. nov.tricuspidatum Assing, 2013 (Lathrobium), spec. nov.triquetrum Assing, 2013 (Lathrobium), spec. nov.zhemoicum Assing, 2013 (Lathrobium), spec. nov.